Luminescence kinetics of alkali halide crystals doped with nitrite anions - Sakun, V.P.; Stashchuk, V.S.; Motrenko, R.M. (Functional Materials, 2006)
The investigation results of the ¹В₁ ➔ ¹А₁ -luminescence decay kinetics of impurity nitrite anions in alkalihalide single crystals are considered. The measurements were carried out at 4.2 К. The connection between the decay time and the structure parameters of the luminescence spectrum is discussed. Розглянуто результати спектрального дослiдження кiнетики загасання фотолюмiнесценцiї ¹В₁ ➔ ¹А₁ домiшкових анiонiв нiтриту в лужно-галоїдних кристалах. Вимiрювання проведено при 4,2 К. Обговорюється зв'язок мiж часом загасання i параметрами структури спектра люмiнесценцiї. Рассмотрены результаты спектрального исследования кинетики затухания фотолюминесценции ¹В₁ ➔ ¹А₁ примесных анионов нитрита в щелочно-галоидных кристаллах. Измерения проведены при 4,2 К. Обсуждается связь между временем затухания и параметрами структуры спектра люминесценции.